The Correlation Between Hyperglycemia and Rheumatoid Factor in Type 2 Diabetic Patients in Al- Risafa Area, Baghdad - K. Mohammed Salih, Raya; M. Al-Gharawi, Ali; I. Al-Lehibi, Khalid (Iraqi Journal of Pharmaceutical Sciences, 2017)
Diabetes mellitus type 2 (T2DM) formerly called non-insulin dependent diabetes mellitus (NIDDM) or adult-onset diabetes is a common disease. Rheumatoid factor is a well-established test used in the diagnosis and follows the prognosis of rheumatoid arthritis (RA). Rheumatoid factor is sometimes found in serum of patients with other diseases including diabetes mellitus (DM), due to the presence of pro-inflammatory cytokines such as TNF- Î± which play an important role in chronic inflammatory and autoimmune diseases like rheumatoid arthritis (RA). The aim of the study is to investigate the associations between type 2 diabetes mellitus (T2DM) and rheumatoid arthritis (RA) in scope of rheumatoid factor (RF), hyperglycemia and body mass index (BMI), in patients with T2DM lived in Al-Risafa area -Baghdad. One hundred twenty five (125) type 2 diabetes mellitus (T2DM) patients were selected from the out patients department of the Specialized Center for Endocrinology and Diabetes, Baghdad; in addition to (70) apparently healthy non diabetic, non arthritic subjects as control, during the period from Sep. - Dec./2010. The ages of both patients and control subjects were within (35-75) years. This study focus to search for the correlation between T2DM and RF "qualitative and quantitative" in relation to body mass index (BMI) and gender. Out of 125 DM-patients (73 female and 52 male), 44 (35.2 %) showed positive RF when compared with healthy controls (N=3, 4.3%). [P value =0.01 is significant] with female dominance (N=28, 63.6%) in compared to males (N=16, 36.4 %), when these diabetics with RF positive were titered for RF (8, 16, 32 and 64 IU/ml), the following results were obtained. The highest percentage of titer observed with 34.1% in those with RF titer 64 IU/ ml [P value = 0.01] when compared with healthy control. 18.2 % had RF titer of 8 IU/ ml, 20.4 % had RF titer of 16 IU/ ml, 27.3 % had RF titer of 32 IU/ ml and 34.1 % had RF titer of 64 IU/ ml. The highest percentage among the overweight, DM patients (38.9 %) have a mean titer 64 IU/ml, a percentage decrease respectively as below: 38.9 % had RF titer of 64 IU/ ml, 27.8% had RF titer of 32 IU/ ml, 16.6 % had RF titer 16 IU / ml and 16.6% had RF titer 8 IU/ ml. The highest number and percentage of DM with RF positive (N=17, 38.6 %) were located among higher age (50-59), (60-69) & (70 -79) year groups (N=17, 38.6%), (N=13, 29.5%) & (N=8, 18.2%) respectively, [P- Value < 0.01] when compared to the corresponding controls. The effect of fasting plasma glucose level of type 2 DM in patients who have RF positive titer, is found that > 7.2 mmol/l glucose in plasma contribute the highest titer (N=28, 63.6 %), in comparison with group of plasma glucose levels < 7.2 mmol/l patients (N=16, 36.4%). with a highly significant difference, P-value = 0.006.Smokers diabetic patients with RF positive (N=27, 61.4%) dominate over non- smokers with RF positive (N=17, 38.6%). The results of this study indicate that there is a reasonable increased frequency of positive rheumatoid factor (RF) in type 2 diabetic patients. Poor glycemic control is associated with higher RF titer in positive cases. The titer of T2DM smoker patients is associated with positive RF values that exceed the titer of the non- smoker RF positive patients. Thus, smoking might not be correlated significantly to DM, but may contribute to its complications. Key words: T2DM, RF, BMI, Smoking.